The relationship between emotional regulation and anger control skills and self-esteem of correctional center adolescents - Khatami, Mahyasadat; Khazaei, Setayesh; Rahmani, Seyedeh Maryam (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: Every year we face a significant increase in juvenile delinquency in many countries and Iran, which has negative psychological consequences for this group; Therefore, the present study was conducted with the aim of determining the relationship between emotional regulation and anger control skills and self-esteem of adolescents in Tehran Correctional Center. Methods: This research was a descriptive-correlational study. The population of this study consisted of all adolescents of the Rehabilitation and Training Center of Tehran in 1607 in 2018. Of these, 113 were selected by simple random sampling. To collect data, emotional regulation, anger control and self-efficacy were used. Data analysis was performed using Pearson correlation coefficient and regression analysis with Spss.22 software. Results: The findings showed that with an increase in the mean (SD) of emotional regulation, the anger control skill decreases (r=0.27, P